KOMPARASI KINERJA ALAT PILE DRIVING ANALYZER DAN SOFTWARE CAPWAP DALAM MENGHASILKAN DAYA DUKUNG ULTIMIT PONDASI TIANG - Rasdinanta Tarigan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2020)
Buildings that stand on soft soil usually use a pile foundation. Testing the ultimate bearing capacity of pile foundations in the field is a Pile Driving Analyzer (PDA) tool. Besides being inexpensive to test, the results can also be known quickly. This tool is supported by a software called CAPWAP (CAse Pile Wave Analysis Program).In this paper, a performance comparison of the Pile Driving Analyzer (PDA) and CAPWAP (CAse Pile Wave Analysis Program) software will be presented in producing the ultimate bearing capacity of pile foundations. The results of both will be analyzed in such a way that the causes of the differences in the performance of the Pile Driving Analyzer (PDA) and the CAPWAP software are known.The results obtained show that the performance of the Pile Driving Analyzer (PDA) tool will not be optimal if the energy transferred to the pile foundation is too small. The energy given by the hammer when struck must be in the range of 1% - 2%, if it is smaller then the performance of the tool in producing the ultimate bearing capacity will not be representative. The difference in the ultimate bearing capacity between the PDA device and the CAPWAP software for energy transferred to the pile foundation (EMX) under the specified energy standard is 10.71% - 33.23%. Meanwhile, energy that meets the specified standards has a value between 0.24% - 1.80%.